Forming of strands at continuous casting into roll mold with bearing rids - E. F. Baranovsky (Литьë и металлургия)
The heat interchange is examined during casting of lead^\ strands, lead alloys and salts into roll mold by means of rolling from the molten condition and by fluid rolling. The influence of casting properties on mechanical characteristics, structure and chemical heterogeneity of strands produced by rolling from the molten condition is investigated. The parameters of the equipment for continuous casting of strands into the roll mold are given.